Porphyromonas spp., Fusobacterium spp., and Bacteroides spp. dominate microbiota in the course of macropod progressive periodontal disease - Sabine Yip (Nature Portfolio, 2021)
Abstract Macropod progressive periodontal disease (MPPD) is a necrotizing, polymicrobial, inflammatory disease commonly diagnosed in captive macropods. MPPD is characterized by gingivitis associated with dental plaque formation, which progresses to periodontitis and then to osteomyelitis of the mandible or maxilla. However, the underlying microbial causes of this disease remain poorly understood. In this study, we collected 27 oral plaque samples and associated clinical records from 22 captive Macropodidae and Potoroidae individuals that were undergoing clinical examination at Adelaide and Monarto Zoos in South Australia (15 healthy, 7 gingivitis and 5 periodontitis-osteomyelitis samples). The V3-V4 region of the 16S ribosomal RNA gene was sequenced using an Illumina Miseq to explore links between MPPD and oral bacteria in these animals. Compositional differences were detected between the microbiota of periodontitis-osteomyelitis cases compared to healthy samples (p-value with Bonferroni correction < 0.01), as well as gingivitis cases compared to healthy samples (p-value with Bonferroni correction < 0.05) using Permutational Multivariate Analysis of Variance (PERMANOVA). An overabundance of Porphyromonas, Fusobacterium, and Bacteroides taxa was also identified in animals with MPPD compared to healthy individuals using linear discriminant analysis effect size (LEfSe; p =  < 0.05). An increased abundance of Desulfomicrobium also was detected in MPPD samples (LEfSe; p < 0.05), which could potentially reflect differences in disease progression. This is the first microbiota analysis of MPPD in captive macropods, and these results support a polymicrobial pathogenesis of MPPD, suggesting that the microbial interactions underpinning MPPD may be more complex than previously documented.